Penerapan Posisi Semi Fowler dalam Meningkatkan Kualitas Tidur dan Mengurangi Sesak Napas pada Pasien Congestive Heart Failure : Studi Kasus Berbasis Evidence-Based Nursing: Implementation of Semi-Fowler Position to Improve Sleep Quality and Reduce Dyspnea in Patients with Congestive Heart Failure : An Evidence-Based Nursing Case Study - Luruk, Ricardo Correia; Xavier, Julieta de Carvalho; Bangun, Argi Virgona; Marpaung, Lilis Suryani (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Congestive Heart Failure (CHF) is a chronic cardiovascular condition frequently accompanied by dyspnea and impaired sleep quality as a result of pulmonary congestion and reduced cardiac output. These symptoms significantly affect patient comfort and quality of life, highlighting the need for effective non-pharmacological nursing interventions. This study aimed to describe the implementation of the semi-Fowler position as an Evidence-Based Nursing (EBN) intervention to reduce dyspnea and improve sleep quality in patients with CHF. This study employed an Evidence-Based Nursing case study design involving one patient diagnosed with CHF who was hospitalized at Immanuel Hospital Bandung. The patient experienced dyspnea and sleep disturbances but was hemodynamically stable and fully conscious. The intervention consisted of positioning the patient in a semi-Fowler position with head-of-bed elevation of 30–45 degrees for approximately 15 minutes once daily over three consecutive days. Data were collected through nursing assessments, direct clinical observation, and evaluation of patient responses before and after the intervention. The findings demonstrated a positive clinical response following the implementation of the semi-Fowler position. The patient reported reduced dyspnea, improved respiratory comfort, and decreased use of accessory muscles during breathing. In addition, improvements were observed in sleep duration and perceived sleep quality, with fewer nocturnal awakenings related to shortness of breath. In conclusion, the semi-Fowler position is an effective, simple, and safe non-pharmacological nursing intervention for reducing dyspnea and improving sleep quality in patients with Congestive Heart Failure . This intervention can be integrated into routine nursing care as part of Evidence-Based Nursing practice to enhance patient comfort and overall quality of life.